Experimental and Numerical Investigation of Residential Furnace Performance with Blends of Natural Gas and Green Hydrogen - Zeinolabedini, Behzad (East Carolina University)
In this study, the impact of hydrogen supplementation on residential furnace performance is examined by doing both experiments and computer simulations. The experimental work examines the performance of furnaces under 15% blends of hydrogen and natural gas. The results reveal flame temperature, wall temperature, heat flux, average air flow temperature, heat transfer, combustion efficiency, and emission gas analysis for furnaces operating under 15% blends of hydrogen and natural gas. Experimental results indicate that hydrogen addition has the potential to enhance thermal intensity but may lead to decreased heat release and thermal energy transfer within the furnace structure at higher concentrations. Examination of emission gas analysis data provides further insights, with the 15% hydrogen blend exhibiting slightly lower emission levels compared to the 0% hydrogen condition, indicating reduced emissions of pollutants such as CO, NO, and NOx. This reduction underscores the environmental benefits of hydrogen addition and its potential contribution to mitigating greenhouse gas emissions from residential heating systems. Meanwhile, the numerical part focuses on the combustion characteristics of hydrogen-enriched natural gas blends, illustrating the effects of hydrogen concentration on maximum flame temperature and combustion efficiency. The addition of hydrogen to natural gas introduces changes in the composition of the fuel mixture, impacting combustion characteristics. The initial increase in the maximum flame temperature, up to a 25% hydrogen concentration, indicates a positive influence on the combustion process. Findings suggest an optimal threshold for hydrogen concentration to achieve peak combustion efficiency, beyond which diminishing returns are observed due to alterations in flame stability. This study highlights the importance of optimizing hydrogen concentration in natural gas blends to maximize combustion efficiency and contribute to a sustainable energy future.
Keywords: Green Hydrogen; Residential Furnace; CFD; H2/NG Blend; Experimental Work; Furnaces--Fuel systems; Furnaces--Efficiency; Hydrogen as fuel; Natural gas; Renewable energy sources